Evaluation of HPRT Gene mutation and Comet Assay in Some Breast Cancer Patients Undergoing Radiotherapy (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Radiotherapy is a toxic cellular treatment that destroys rapidly dividing cells such as cancercells. The strategy for HPRT mutation examination in human’s cells was commonly used to establish in vivohistory along with mutation rates in children and adults inhabitants subjected to experienced and unfamiliarexternal mutagens. As just a practical approach to human biosurveillance studies, the comet assay hasbeen introduced over the past years as biomarker to identify ionizing radiation Consequences with Patientsundergoing radiotherapy in breast cancer.Materials and Method: This study was carried out on thirty Iraqi women patients with BC patientsundergoing radiotherapy about 20-30 Gy locally gamma cells at Al-Amel National Hospital for cancerManagement in Baghdad during time 2-13 years, non-smokers and non- alcoholic, aged (35-55 year),with stage (grade) I-III, as well as thirty apparently healthy individuals females collected randomly frompopulation living Baghdad, Old age (35-55) Which are non-alcoholic non-smokers as group of control.Around the ongoing research comet-test and hprt mutation test could be applied to study damages in DNAfor genetic two endpoints For patients with cancer throughout radiation therapy.Results: The present study showed significant increase (p<0.05) in the HPRT gene mutation assay for thein breast cancer patients undergoing radiotherapy as compared with the control group. Also there werefound that the values of comet tail moment and tail length was increased significantly (p<0.05) in the humanlymphocyte in these for breast cancer patients undergoing radiotherapy as compared with the control group.Conclusions: Present results revealed that there is a probability of utilizing human lymphocytes changes asuseful biodosimetric markers for the detection of human exposure to ionizing radiation, the data gatheredalso demonstrated the utility of the HPRT gene mutation and (Alkaline) comet test as just a precise alternativebiological marker for routine preventative care of cancer patients receiving radiation therapy.